Assessment on growth pattern of Khasi children in the state of Meghalaya, India - Warjri, Barikor C. (International Journal of Research in Medical Sciences, 2016)
Background: This paper makes an attempt to describe the growth pattern and their sexual differences among the Khasi tribe in the state of Meghalaya in India. In the study we include 495 girls and 557 boys aged 3 to 18 years. Methods: In this Study the weight and height of these children were taken. Preece-Baines model 1 (PB1) has been used. This model was adopted for fitting the means of weight and some important linear measurements (Preece and Baines 1978), 1 using Levenberg-Marquardt method through SPSS (version 17.0) and origin software (version 8.0) for windows. All data were managed and analyzed using SPSS/PC software, version 15, in which the level of significance was set at 15%. The analysis will be carried out to present the basic descriptive statistics of anthropometric variables viz., height, weight, etc. according to sex and age groups. Results: The growth pattern of the Khasi children in the present study are described in terms of anthropometric measurement is observed that girls are heavier than boys at 3 and 4 years of age and boys are significantly heavier than girls from 5 to 6 years old. However girls are heavier than boys at the age of 12 years of age. It is further observed that boys are significantly heavier than girls and are statistically significant, except at the age of 15. It is found that both boys and girls are more or less similar in weight from 7 to 12 years of age. Conclusions: In terms of height boys are generally taller than girls across ages except at adolescence from 11 to 12 years where girls are taller than boys. The differences between the sexes are statistically significant after 14 years of age; the estimate values for adult height are 157.5 in males and 152 in females.